HUMAN RESOURCE MANAGEMENT FOR SUSTAINABLE DEVELOPMENT GOALS (SDGS): A SYSTEMATIC LITERATURE REVIEW - Yasadani; Zulpaini Tanjung; Ihsanul Anhar; Ahmad; Fachrurrozi; Rakesh Sitepu; Anggia Sari Lubis (CV. Radja Publika, 2025)
The Sustainable Development Goals (SDGs) mandated by the United Nations demand a global commitment, including from the corporate sector, to achieve social, economic, and environmental targets by 2030. Human Resource Management (HRM) plays a crucial role as the main agent of change in integrating sustainability principles into organizational operations. This research aims to analyze the strategic role of HRM functions ranging from recruitment, training and development, to performance management and compensation in supporting the achievement of the SDGs, particularly SDG 4 (Quality Education), SDG 5 (Gender Equality), and SDG 8 (Decent Work and Economic Growth). The strategies discussed include the implementation of green skills training programs, equal pay policies, and performance measurement based on social impact. The research findings conclude that the transformation of HRM towards sustainability-focused practices not only enhances corporate image and employee engagement but also directly contributes to the achievement of global sustainable development goals.